Title the Function of Pottery in the Iban Community in Sibu’s Longhouse, Sarawak - Anak Anggo, Fujica; Laja, Louis; Binti Abu Bakar, Rohana (International Journal of Engineering and Technology, 2018)
Tajau or more commonly known as pot is an inherited heritage for generations by the Iban in Sarawak. It is made ofÂ clay and each tajau has its own uniqueness in terms of sculpture, height, size, shape and color. Tajau also become a symbol of wealth in the family. Owners who have a lot tajau number often associated with wealth and generosity ofÂ the food especially when tajau filled with rice. Moreover, tajau have a variety of functions in everyday life Iban use. The research is based on the function, beliefs, taboos and other types of tajau.Â Â